A onomasiologia e seus dicionários: o caso do Dicionário onomasiológico de expressões cromáticas da fauna e flora - Martins, Sabrina de Cássia [UNESP]; Zavaglia, Claudia [UNESP] (My University, 2014)
Nowadays, the lexicographical market has experienced an increase of the number of works produced. These works belong to two forms of macro-structural organization: the semasiological one and onomasiological one. This study aims at considering the qualities and advantages of onomasiological dictionaries, as well as defending that semasiology and onomasiology establish an intrinsic relationship that should be considered in the development of dictionaries. In order to demonstrate the benefits provided by a combination of onomasiological and semasiological courses in the same work, we describe how such courses were adopted in the Onomasiological Dictionary of Chromatic Phrases from Fauna and Flora.

Atualmente, o mercado lexicográfico tem vivenciado um aumento no que diz respeito ao número de obras produzidas. Tais obras se enquadram em duas formas de organização macroestrutural: a semasiológica e a onomasiológica. O presente trabalho tem como objetivo atentar para as qualidades e vantagens das obras onomasiológicas, além de defender que Semasiologia e Onomasiologia estabelecem uma relação intrínseca que deve ser considerada na elaboração de dicionários. A fim de demonstrar os benefícios proporcionados pela combinação dos percursos onomasiológico e semasiológico em uma mesma obra, descreveremos como os adotamos no Dicionário Onomasiológico de Expressões Cromáticas da Fauna e da Flora.
The onomasiological dictionary of chromatic phrases of fauna and flora
Keywords: Dicionários onomasiológicos; Onomasiologia e Semasiologia; percurso onomasiológico e percurso semasiológico; onomasiological dictionaries; onomasiology and semasiology; onomasiological perspective and semasiological perspective